The Influence of Premium Materials and Design Innovation on Erigo Brand Competitiveness in the Global Market - Tyo Azharil Fikri; Nurlaila; Marliyah (LP2M IAIN Palopo, 2025)
This study examines the influence of premium materials and design innovation on the competitiveness of the Erigo brand in the global market. The method used is descriptive quantitative, with a sample of 100 students from the Faculty of Economics and Islamic Business, UINSU. Data analysis was conducted using multiple linear regression through SPSS. The results indicate that premium materials and design innovation have a positive and significant effect on Erigo's competitiveness. These findings highlight the importance of material quality and product innovation in enhancing the position of local brands in the international market.